Fenomena Kerusakan Lingkungan di Tana Toraja: Analisis Kritis terhadap Tugas Manusia sebagai Mandataris Allah dalam Menjaga dan Mengelola Kelestarian Alam Semesta berdasarkan Kitab Kejadian 2:15 - Bartolomius Budi; Hardi Saputra; Ronaldo Stefanus; Rinto Paratu; Jhon Teka (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2026)
Landslides and floods are common occurrences in human life; however, it is crucial to reflect on and acknowledge that the underlying causes of these events often stem from human attitudes specifically, how humans fulfill their role as God’s stewards. This study employs a descriptive qualitative method with a literature-based approach to analyze the issue at hand. It aims to describe the human mandate derived from Genesis 2:15 to preserve and manage the sustainability of the universe, while also critiquing human actions that exploit nature and subsequently harm human life itself. The findings indicate that humans, as God’s creation and recipients of the mandate outlined in Genesis 2:15, bear the responsibility of safeguarding and maintaining the natural world inhabited by all living beings, including themselves. Because such disasters adversely affect human life, there is a need for an attitude of care and love toward the universe the creation God has entrusted to us. The universe must serve as a home for all living beings; humans share a bond and relationship with all of God’s creation within it, and all exist in a state of mutual interdependence.